THE FALL OF MAN IN SHAKESPEARE’S MACBETH COMPARING TO THAT IN A CREATION STORY: A STUDY FROM QUR’ANIC PERSPECTIVE - MIRZA, SANAA’ SA’EED (Journal of Duhok University, 2020)
Inspired and motivated by our conviction that “Shakespeare is a gift of Heaven to all of Mankind, for every creed, in every age" (Lings, 1998, 12), this research aims at studying William Shakespeare’s Macbeth from a Qur’anic perspective instead of a biblical one, as has usually been done so far. The study utilizes Islamic pedagogy to examine Macbeth, a European masterpiece, hypothesizing that Islam offers a uniquely different view of the world from that of the European one. For its textual analysis, the study relies on verses translated from the Noble Qur’an as well as Hadiths (the prophet’s traditions) from Sunnah, in addition to the text of Macbeth. The axiomatic question that is raised here is whether or not we have the right to categorize Shakespeare’s Macbeth into “sacred art”. The study answers positively to this question since the thematic framework of the play revolves around “the essence of religion” (Lings, 1998, 12). The study attempts to analyze and compare the fall of man in Shakespeare’s Macbeth to that in the story of man’s creation from Qur’anic perspective according to five axes. The first axis is about the temptation of the evil power in both stories, Adam’s creation in Quran and Shakespeare’s Macbeth. The second axis examines the role of Hawaa (Eve) and Lady Macbeth as temptresses. The third axis is about the feeling of remorse for the evil actions that they take and the punishment of God. The fourth axis presents a study of the nature of some encounters between humanity and evil forces. The fifth axis presents a brief study of the types of human soul (Nafs) from Quranic perspective to diagnose the role of the soul in determining the characteristics of each personality. Yet, the study concludes that Shakespeare presents Macbeth with a narrow perspective to represent only the inherent weakness of humanity in the face of evil forces, ignoring his charitable nature to encounter evil forces, and his fall is cursed eternally because of his insistence on evil; while Adam (peace be upon him) represents humanity in all of his conditions, and his fall is not eternal because of his remorse and repentance.